Fe (II) spin crossover material based on perchlorate and preparation method and application of Fe (II) spin crossover material
By using Fe(II) spin cross material of perchlorate [Fe(bamp)2]·(ClO4)2 under anaerobic conditions, the problem of difficult room temperature self-rotation in the prior art is solved, and high efficiency is achieved Prepare materials with self-rotation change and wide hysteresis loops, suitable for molecular switches and information storage.
Patent Information
- Application Number
- CN202411337560.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The self-spinning phenomenon of existing spin-crossing materials at room temperature is difficult to achieve, and there are only a handful of compounds that have room temperature self-spinning and wide hysteresis loops.
Fe(II) spin cross material [Fe(bamp)2]·(ClO4)2 of perchlorate, by using 2,6-bis(aminomethyl)pyridine and ferrous perchlorate under anaerobic conditions Stir, filter and evaporate in a hot solvent to obtain a dark red crystal.
The preparation of Fe(II) spin cross material with room temperature self-rotation change and wide hysteresis loop is achieved. It has the characteristics of inexpensive raw materials, stable structure and performance, and is suitable for molecular switches and information storage fields.
Smart Images

Figure CN119431223A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new materials, and in particular relates to a perchlorate-based Fe(II) spin crossover material and a preparation method and application thereof. Background Art
[0002] Spin crossover materials are one of the hottest topics in the field of magnetic research. The occurrence of spin transition is often accompanied by changes in spin state, structure, magnetism and color. Therefore, it has a wide range of application value in micro / nano materials such as molecular sensors, molecular switches, information memory storage and displays. When spin transition occurs near room temperature, it can be used in computer information storage and room temperature molecular switches. However, the transition temperature of most spin transition compounds is lower than room temperature, which makes it difficult to realize the application in materials. Therefore, it is still very necessary to synthesize compounds with room temperature spin transition and wide hysteresis loop. At present, dozens of room temperature spin crossover complexes have been reported, but only a few can be used in practice. The occurrence of spin transition requires appropriate ligand field strength. Generally, strong fields tend to low spin states, and weak fields tend to high spin states. Counter anions in the lattice, ligand substituents and crystallization solvent molecules can have an important influence on the coordination synergy, resulting in gradual changes, sudden changes and hysteresis loops in the metal spin center.
[0003] Counter anions have an important influence on the coordination synergy of spin transitions. Different anions may cause different stacking and hydrogen bonding modes in the crystal. Studies have reported a mononuclear Fe(II) spin transition complex [Fe(2-pic)3]·A2·Solv with three different anions, where A contains m-aminobenzenesulfonic acid, p-aminobenzenesulfonic acid, and trifluoromethanesulfonic acid, 1-pic=2-picolylamine. Different counter anion complexes produce different stacking structures due to hydrogen bonding, which has a very significant effect on the coordination synergy of the spin transition center and plays a regulatory role in the temperature, type and hysteresis loop width of the spin transition. However, the rational design and precise control of these intermolecular interactions remain a major challenge. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a perchlorate-based Fe(II) spin-crossover material, wherein the chemical structural formula of the Fe(II) spin-crossover material is [Fe(bamp)2]·(ClO4)2;
[0007] In the formula, bamp represents 2,6-bis(aminomethyl)pyridine;
[0008] The crystal structure of the Fe(II) spin-crossing material is monoclinic, the space group is P21 / c, and the unit cell parameters are: α=90°,β=98.688(2)°,γ=90°, the Fe-N bond length range is
[0009] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing the perchlorate-based Fe(II) spin crossover material.
[0010] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0011] The preparation method is carried out under anaerobic conditions and comprises:
[0012] 2,6-bis(aminomethyl)pyridine is added to a hot solvent to obtain solution I;
[0013] Perchlorate and ferrous salt are added to hot solvent to obtain solution II;
[0014] Solution II is added to solution I, and the mixture is stirred, filtered, and evaporated in sequence. The precipitated dark red crystals are Fe(II) spin-crossover materials.
[0015] As a preferred embodiment of the method for preparing the perchlorate-based Fe(II) spin crossover material of the present invention, the hot solvent is a solvent deoxygenated by passing nitrogen for 12 to 24 hours, and the temperature is 30 to 60°C.
[0016] As a preferred solution of the method for preparing the perchlorate-based Fe(II) spin crossover material of the present invention, the hot solvent is obtained by mixing one or two solvents selected from deionized water, methanol or ethanol.
[0017] As a preferred embodiment of the method for preparing the perchlorate-based Fe(II) spin crossover material of the present invention, when the hot solvent is obtained by mixing two solvents, the mixing volume ratio of the two solvents is 1:0.25-4.
[0018] As a preferred embodiment of the method for preparing the perchlorate-based Fe(II) spin crossover material of the present invention, the concentration of perchlorate in the solution II is 0.15-0.35 mol / L.
[0019] As a preferred scheme of the preparation method of the perchlorate-based Fe(II) spin crossover material described in the present invention, the molar ratio of the 2,6-bis(aminomethyl)pyridine to the perchlorate is 2:1 to 1.2, and the molar ratio of the perchlorate to the ferrous salt is 1 to 2:1.
[0020] As a preferred embodiment of the method for preparing the perchlorate-based Fe(II) spin crossover material of the present invention, the perchlorate comprises one or both of ferrous perchlorate and sodium perchlorate.
[0021] As a preferred embodiment of the method for preparing the perchlorate-based Fe(II) spin crossover material of the present invention, the ferrous salt comprises one or both of ferrous perchlorate and ferrous chloride.
[0022] Another object of the present invention is to overcome the deficiencies in the prior art and provide the application of the perchlorate-based Fe(II) spin crossover material in information storage and molecular switches.
[0023] Beneficial effects of the present invention:
[0024] (1) Compared with high-temperature and high-pressure solvent thermal synthesis, poor solvent diffusion and other methods, the method of preparing materials by volatilization at room temperature of the present invention has the advantages of simple reaction conditions and easy implementation.
[0025] (2) The organic ligand 2,6-bis(aminomethyl)pyridine in the present invention has abundant phenyl groups and amino groups, which can easily construct π-π stacking and hydrogen bonding to finely control the spin transition properties; at the same time, ClO4 - The regulation enhances the π-π intermolecular stacking effect, and the synergistic effect of the two causes the material to exhibit spin transition behavior.
[0026] (3) The present invention achieves a higher yield of [Fe(bamp)2]·(ClO4)2 by exploring the effects of solvent type and temperature, and the amount of ferrous perchlorate added on the yield of Fe(II) spin crossover magnetic material [Fe(bamp)2]·(ClO4)2.
[0027] (4) The Fe(II) spin-crossover magnetic material [Fe(bamp)2]·(ClO4)2 disclosed in the present invention has the characteristics of cheap raw materials, stable structure and performance. The synthesized spin-crossover material can be applied to the fields of molecular switches and information storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0029] Figure 1 This is the crystal structure diagram of [Fe(bamp)2]·(ClO4)2 in Example 1 of the present invention.
[0030] Figure 2 This is a stacking diagram of the crystal structure of [Fe(bamp)2]·(ClO4)2 in Example 1 of the present invention.
[0031] Figure 3 This is the powder X-ray diffraction pattern of [Fe(bamp)2]·(ClO4)2 in Example 1 of the present invention.
[0032] Figure 4 This is a temperature-dependent magnetic susceptibility curve of [Fe(bamp)2]·(ClO4)2 in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0036] The reagents used in the present invention are all commercially available and analytically pure. Except for the solvent which is deoxygenated, other reagents are not further purified before use.
[0037] Example 1
[0038] This embodiment provides a method for preparing a Fe(II) spin crossover magnetic material:
[0039] Deionized water at 60° C. was placed in a Schlenk bottle, and nitrogen was bubbled into the solvent through a gas guide tube for 24 hours to obtain an oxygen-free water solvent.
[0040] In a glove box, 0.6 mmol of organic ligand bamp (2,6-bis(aminomethyl)pyridine) was added to 2 mL of oxygen-free water solvent and stirred to dissolve.
[0041] Then in the glove box, add 0.35 mmol of ferrous perchlorate into 2 mL of water and stir to dissolve. Note that ferrous perchlorate needs to be weighed with a plastic spoon.
[0042] Slowly add the ferrous perchlorate aqueous solution to the organic ligand solution and stir for 10 minutes at room temperature 25°C. Filter and evaporate statically. After two weeks, dark red block crystals suitable for X-ray diffraction will precipitate, which is the divalent iron complex [Fe(bamp)2]·(ClO4)2.
[0043] The yield of [Fe(bamp)2]·(ClO4)2 was 68%.
[0044] The specific characteristics of [Fe(bamp)2]·ClO4)2 prepared in this Example 1 are as follows:
[0045] (1) Crystal structure determination. The instrument used for single crystal testing is Apex Duo single crystal diffractometer, and the radiation source is Mo-Kα radiation from a graphite monochromator. The single crystal analysis data is shown in Table 1.
[0046] Table 1 Crystal data and structure refinement parameters of the complex [Fe(bamp)2] system
[0047]
[0048]
[0049] Based on the test results of the crystal structure parameters in Table 1, Figure 1 and Figure 2 The molecular structure of the complex [Fe(bamp)2]·(ClO4)2 is shown in Figure 2. The complex [Fe(bamp)2]·(ClO4)2 belongs to the monoclinic system and the space group is P21 / c. In the smallest asymmetric unit of the complex [Fe(bamp)2]·(ClO4)2, there are 2 [Fe(bamp)2] 2+ Cationic center, four ClO4 - Anion: Fe 2+ The metal center is coordinated with two organic ligands to form a distorted octahedral structure via six coordinating nitrogen atoms.
[0050] The octahedral configuration can be obtained by calculating the coordination environment of the metal center using SHAPE 2.1. As shown in Table 2, the two hexacoordinated Fe(II) metal centers are most likely to have an octahedral configuration. From the stacking structure, it can be seen that there is a face-to-face π-π stacking interaction between the phenyl groups of the ligand bamp, and the distance between the centers is The dihedral angle is 2.56°, which is close to parallel.
[0051] Table 2Fe 2+ Some calculated data of ion coordination configuration
[0052]
[0053] Note: HP is hexagon, PPY is pentagonal pyramid, OC is octahedron, TPR is triangular prism, and JPPY is Johnson pentagonal pyramid.
[0054] Table 3 shows the coordination bond lengths of the metal center in the complex [Fe(bamp)2] system.
[0055] Table 3 Coordination bond lengths of metal centers in the complex [Fe(bamp)2] system
[0056]
[0057] From Table 3, we can see that the Fe1-N coordination bond length is The Fe2-N coordination bond length is This indicates that both Fe1 and Fe2 are relatively long at 298 K, corresponding to the high spin state of Fe(II) ions.
[0058] (2) Powder X-ray diffraction determination of phase purity
[0059] The phase purity of the crystalline product obtained in this example was characterized using Rigaku's MiniFlex 600c powder X-ray diffractometer. The theoretical data was obtained by simulating the single crystal structure using Mercury software. The results are shown in Figure 3 As shown, it can be seen that the experimental value of the diffraction peak of the complex obtained in this example is very consistent with the diffraction peak of the single crystal structure simulation, indicating that the material has a high phase purity.
[0060] (3) Magnetic properties characterization
[0061] The magnetic measurement uses the superconducting quantum interference device Quantum DesignMPMS SQUID VSM magnetic measurement system, and the antimagnetic correction is processed by Pascal constant. The test temperature of DC magnetic susceptibility is 2~300K, the magnetic field is 1000Oe, and the polycrystalline samples are tested in different temperature ranges, such as Figure 4As shown. It can be seen that the complex [Fe(bamp)2]·(ClO4)2 has a spin transition phenomenon. At 300K, the χ M The T value is 3.24, close to the high spin state of hexacoordinated divalent iron (Fe(II) 5 The high spin theoretical value of T2, S = 2) is 3 cm 3 mol -1 K. As the temperature is cooled from 300K to 50K, the χ M The T value gradually decreases to 1.78cm 3 mol -1 K, partial spin transition behavior is achieved, and the transition temperature is 134 K. When the temperature is lower than 45 K, the value of the magnetic susceptibility continues to decrease, which is due to the influence of high spin zero-field splitting rather than further spin transition.
[0062] In this embodiment, a spin-crossed crystalline material having a π-π stacking structure is synthesized by using (2,6-bis(aminomethyl)pyridine) and ferrous perchlorate in a deionized environment with simple room temperature stirring.
[0063] Example 2
[0064] This embodiment provides a method for preparing a Fe(II) spin crossover magnetic material:
[0065] Methanol at 40° C. and deionized water at 60° C. were respectively placed in Schlenk bottles, and nitrogen was bubbled into the solvent through a gas tube for 24 hours to obtain an oxygen-free solvent.
[0066] In a glove box, 0.6 mmol of organic ligand bamp (2,6-bis(aminomethyl)pyridine) was added to 2 mL of a mixed solvent of oxygen-free methanol and deionized water (volume ratio 1:1) and stirred to dissolve.
[0067] Then, in the glove box, add 0.3 mmol of ferrous perchlorate to 2 mL of water and stir to dissolve. Note that ferrous perchlorate needs to be weighed with a plastic spoon.
[0068] The ferrous perchlorate aqueous solution obtained above was slowly added to the organic ligand solution and stirred at room temperature of 25°C for 10 minutes. After filtration and evaporation, dark red block crystals suitable for X-ray diffraction were precipitated after two weeks, which was the divalent iron complex [Fe(bamp)2]·(ClO4)2.
[0069] The yield of [Fe(bamp)2]·(ClO4)2 was 23%, which was significantly lower than that in Example 1.
[0070] Example 3
[0071] This embodiment provides a method for preparing a Fe(II) spin crossover magnetic material:
[0072] Ethanol at 50° C. and deionized water at 60° C. were placed in a Schlenk bottle, and nitrogen was bubbled into the solvent through a gas tube for 24 hours to obtain an oxygen-free solvent.
[0073] In a glove box, 0.6 mmol of organic ligand bamp (2,6-bis(aminomethyl)pyridine) was added to 2 mL of a mixed solvent of oxygen-free ethanol and deionized water (volume ratio 1:1) and stirred to dissolve at room temperature.
[0074] Then, in the glove box, add 0.3 mmol of ferrous perchlorate to 2 mL of water and stir to dissolve at room temperature. Note that ferrous perchlorate needs to be weighed with a plastic spoon.
[0075] The ferrous perchlorate aqueous solution obtained above was slowly added to the organic ligand solution and stirred at room temperature of 25°C for 10 minutes. After filtration and evaporation, dark red block crystals suitable for X-ray diffraction were precipitated after two weeks, which was the divalent iron complex [Fe(bamp)2]·(ClO4)2.
[0076] The yield of [Fe(bamp)2]·(ClO4)2 was 12%, which was significantly lower than that in Example 1.
[0077] Example 4
[0078] This embodiment provides a method for preparing a Fe(II) spin crossover magnetic material:
[0079] Methanol at 40° C. was placed in a Schlenk bottle, and nitrogen was bubbled into the solvent through a gas tube for 24 hours to obtain oxygen-free methanol.
[0080] In a glove box, 0.6 mmol of an organic ligand bamp (2,6-bis(aminomethyl)pyridine) was added to 2 mL of oxygen-free methanol and stirred to dissolve.
[0081] Then, in the glove box, add 0.3 mmol of ferrous perchlorate to 2 mL of oxygen-free methanol and stir to dissolve. Note that ferrous perchlorate needs to be weighed with a plastic spoon.
[0082] The ferrous perchlorate solution obtained above was slowly added to the organic ligand solution, and stirred at room temperature of 25°C for 10 minutes. Filtered, and allowed to evaporate statically, after two weeks, dark red block crystals suitable for X-ray diffraction were precipitated, which was the divalent iron complex [Fe(bamp)2]·(ClO4)2.
[0083] The yield of [Fe(bamp)2]·(ClO4)2 was 34%.
[0084] Example 5
[0085] This embodiment provides a method for preparing a Fe(II) spin crossover magnetic material:
[0086] Ethanol at 40° C. was placed in a Schlenk bottle, and nitrogen was bubbled into the solvent through a gas tube for 24 hours to obtain oxygen-free ethanol.
[0087] In a glove box, 0.6 mmol of an organic ligand bamp (2,6-bis(aminomethyl)pyridine) was added to 2 mL of oxygen-free ethanol and stirred to dissolve.
[0088] Then, in the glove box, add 0.3 mmol of ferrous perchlorate to 2 mL of oxygen-free ethanol and stir to dissolve. Note that ferrous perchlorate needs to be weighed with a plastic spoon.
[0089] The ferrous perchlorate solution obtained above was slowly added to the organic ligand solution, and stirred at room temperature of 25°C for 10 minutes. Filtered, and allowed to evaporate statically, after two weeks, dark red block crystals suitable for X-ray diffraction were precipitated, which was the divalent iron complex [Fe(bamp)2]·(ClO4)2.
[0090] The yield of [Fe(bamp)2]·(ClO4)2 was 29%.
[0091] Example 6
[0092] This embodiment provides a method for preparing a Fe(II) spin crossover magnetic material:
[0093] Deionized water at 60° C. was placed in a Schlenk bottle, and nitrogen was bubbled into the solvent through a gas guide tube for 24 hours to obtain an oxygen-free water solvent.
[0094] In a glove box, 0.6 mmol of organic ligand bamp (2,6-bis(aminomethyl)pyridine) was added to 2 mL of oxygen-free water solvent and dissolved by stirring at room temperature.
[0095] Then, in the glove box, add 0.3 mmol of ferrous perchlorate to 2 mL of water and stir to dissolve at room temperature. Note that ferrous perchlorate needs to be weighed with a plastic spoon.
[0096] The ferrous perchlorate aqueous solution obtained above was slowly added to the organic ligand solution, stirred at room temperature for 10 minutes, filtered, and evaporated statically. After two weeks, dark red block crystals suitable for X-ray diffraction were precipitated, which was the divalent iron complex [Fe(bamp)2]·(ClO4)2.
[0097] The yield of [Fe(bamp)2]·(ClO4)2 was 55%.
[0098] Example 7
[0099] This embodiment provides a method for preparing a Fe(II) spin crossover magnetic material:
[0100] Deionized water at 60° C. was placed in a Schlenk bottle, and nitrogen was bubbled into the solvent through a gas guide tube for 24 hours to obtain an oxygen-free water solvent.
[0101] In a glove box, 0.6 mmol of organic ligand bamp (2,6-bis(aminomethyl)pyridine) was added to 2 mL of oxygen-free water solvent and dissolved by stirring at room temperature.
[0102] Then, in a glove box, 0.35 mmol of ferrous chloride and 0.7 mmol of sodium perchlorate were added to 2 mL of water and dissolved by stirring at room temperature.
[0103] The ferrous perchlorate aqueous solution obtained above was slowly added to the organic ligand solution, stirred at room temperature for 10 minutes, filtered, and evaporated statically. After two weeks, dark red block crystals suitable for X-ray diffraction were precipitated, which was the divalent iron complex [Fe(bamp)2]·(ClO4)2, with a yield of 41%.
[0104] Comparative Example 1
[0105] The difference between this comparative example and Example 1 is that no deoxygenation treatment is performed by introducing nitrogen.
[0106] After 1 day of static evaporation, the solution turned red, and no crystals were precipitated until the solvent evaporated, indicating that the Fe(II) spin-crossed magnetic material could not be successfully synthesized.
[0107] Comparative Example 2
[0108] The difference between this comparative example and Example 1 is that all operations are carried out in an outdoor fume hood.
[0109] After 1 day of static evaporation, the solution turned red and turbid. When the solvent evaporated to dryness, no crystals were precipitated, which means that the Fe(II) spin-crossed magnetic material could not be synthesized.
[0110] Comparative Example 3
[0111] The difference between this comparative example and Example 1 is that the amount of ferrous perchlorate added is adjusted to 0.6 mmol, that is, the molar ratio of bamp to ferrous perchlorate is 1:1, and the yield of the synthesized complex crystal material is extremely low, only 4%.
[0112] Comparative Example 4
[0113] The difference between this comparative example and Example 1 is that the amount of ferrous perchlorate added is adjusted to 0.2 mmol, that is, the molar ratio of bamp to ferrous perchlorate is 3:1, and the yield of the synthesized complex crystal material is extremely low, close to 0.
[0114] In summary, the room temperature volatilization preparation method of the present invention has the advantages of simple reaction conditions and easy implementation compared with high temperature and high pressure solvent thermal synthesis, poor solvent solvent diffusion and other methods. The organic ligand 2,6-bis(aminomethyl)pyridine has abundant phenyl groups and amino groups, which is easy to construct π-π stacking and hydrogen bonding to finely control the spin transition properties; at the same time, ClO4 - The regulation enhances the π-π intermolecular stacking effect, and the synergistic effect of the two causes the material to exhibit spin transition behavior; by exploring the effects of the type and temperature of the solvent and the amount of ferrous perchlorate added on the yield of the Fe(II) spin-crossover magnetic material [Fe(bamp)2]·(ClO4)2, a higher yield of [Fe(bamp)2]·(ClO4)2 is achieved. The Fe(II) spin-crossover magnetic material [Fe(bamp)2]·(ClO4)2 of the present invention has the characteristics of cheap raw materials, stable structure and performance, and the synthesized spin-crossover material can be applied to the fields of molecular switches and information storage.
[0115] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A perchlorate-based Fe(II) spin crossover material, characterized in that: The chemical formula of the Fe(II) spin cross material is [Fe(bamp)2]·(ClO4)2; In the formula, bamp represents 2,6-bis(aminomethyl)pyridine; The crystal structure of the Fe(II) spin-crossing material is monoclinic, the space group is P21 / c, and the unit cell parameters are: α=90°,β=98.688(2) o ,γ=90o, the Fe-N bond length range is 2. The method for preparing the perchlorate-based Fe(II) spin crossover material according to claim 1, characterized in that: The preparation method is carried out under anaerobic conditions and comprises: 2,6-bis(aminomethyl)pyridine is added to a hot solvent to obtain solution I; Perchlorate and ferrous salt are added to hot solvent to obtain solution II; Solution II is added to solution I, and the mixture is stirred, filtered, and evaporated in sequence. The precipitated dark red crystals are Fe(II) spin-crossover materials.
3. The method for preparing the perchlorate-based Fe(II) spin crossover material according to claim 2, characterized in that: The hot solvent is a solvent that has been deoxygenated by passing nitrogen for 12 to 24 hours, and the temperature is 30 to 60°C.
4. The method for preparing the perchlorate-based Fe(II) spin crossover material according to claim 3, characterized in that: The hot solvent is obtained by mixing one or two solvents selected from deionized water, methanol or ethanol.
5. The method for preparing the perchlorate-based Fe(II) spin crossover material according to claim 4, characterized in that: When the hot solvent is obtained by mixing two solvents, the mixing volume ratio of the two solvents is 1:0.25-4.
6. The method for preparing the perchlorate-based Fe(II) spin crossover material according to claim 2, characterized in that: The concentration of perchlorate in the solution II is 0.15-0.35 mol / L.
7. The method for preparing the perchlorate-based Fe(II) spin crossover material according to claim 2, characterized in that: The molar ratio of the 2,6-bis(aminomethyl)pyridine to the perchlorate is 2:1-1.2, and the molar ratio of the perchlorate to the ferrous salt is 1-2:
1.
8. The method for preparing the perchlorate-based Fe(II) spin crossover material according to claim 7, characterized in that: The perchlorate includes one or both of ferrous perchlorate and sodium perchlorate.
9. The method for preparing the perchlorate-based Fe(II) spin crossover material according to claim 7, characterized in that: The ferrous salt includes one or both of ferrous perchlorate and ferrous chloride.
10. Application of the perchlorate-based Fe(II) spin crossover material as claimed in claim 1 in information storage, molecular switches and molecular sensors.
Citation Information
Patent Citations
Spin-crossover conductive difunctional complex, preparation method and application of spin-crossover conductive difunctional complex
CN118359586A
Flexible alkyl chain modified spin crossover complex as well as preparation method and application thereof
CN118561927A